Yield response of durum (Triticum durum) and bread wheat (T. aestivum) varieties to carbon dioxide enrichment - RAVI, I; KHAN, F A; SHARMA-NATU, POONAM; GHILDIYAL, M C (The Indian Journal of Agricultural Sciences, 2014)
In an experiment conducted during the winter season of 1996-97 and 1997-98, 2 varieties (’HD 4502’ and ’B 4409’) of durum wheat (Triticum durum Desf.) and 2 (Kalyansona’ and Kundan’) of bread wheat (T. aestivum L. emend. Fiori & Paol.) were grown in field at atmospheric and elevated Co2 (650 +-50 ppm) concentrations inside open top chambers to examine yield compenents at maturity. The CO2 enrichment enhanced the grain yield mostly through an increase in the number of ear-bearing tillers. Individual ear weight was also increased in plants grown under elevated CO2 concentration. Varieties however differed in the manner, the individual ear weight was creased. In ’B 449’ and ’Kalyansona’, the inccrease in grain yield of individual ear of plants grown under elevated CO2 concentration was due to an increase in individual grain weight. In ’HD 4502’, an increase in grain yield of individual car of plants grown under elevated Co2 concentration was due to higher/ear as a result of increase in spikelets/ear. Genotypic differences in response to elevated CO2 were observed. Varieties having greater sink capacity in terms of higher grains/ear showed greater yield reponse in both terraploid and hexaploid wheat.